PENGARUH IMPLANTASI ION KHROM TERHADAP KEKERASAN, STRUKTUR MIKRO, DAN LAJU KOROSI DALAM MEDIA CAIRAN PBS PADA BAJA STAINLESS STEEL AISI 316 L - , Bangun Pribadi; , Dr. Eng. Priyo Tri Iswanto, ST, M. Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this research is to study the influence of cromium ion implantation on the hardness, microstructure, and corrosion rate of AISI 316L stainless steel in PBS (Phosphate Buffer Saline) solution. Chrome layer can be formed by chromium ion implantation into AISI 316 L stainless steel surfaces. Parameters used in this research are time of implantation such as 3.5, 4.5, 5.5, 6.5, and 7.5 hours, 20 ÂµA of the beam current , and 100 keV of the ions energy. Hardness surface for implanted and unimplanted samples were tested using micro vickers hardness. Corrosion test in PBS solution was carried out using three cell electrodes. The result showes that the surface hardness of raw material is in order of 133.5 VHN0,01, while the optimum hardness is in order of 262.76 VHN0,01 or there is an increasing of hardness in order of 97 % . This optimum hardness was achieved for 5.5 hours of implantataion time or at 4.31x1017ion/cm2 of ions dose. At this conditions, the corrosion rate decreases from from 137.88 mpy to 98.99 mpy or there is a decreasing of corrosion rate in ordert of 39%.